Influence of Indigenous Radio Programme Contents on Voters’ Participation and Voting Patterns in 2015 and 2019 Governorship Elections in Oyo State (Global Journal of Human-Social Science, 2025)
Several radio stations in South-Western Nigeria feature different indigenous radio programmes that contribute to the dissemination of diverse electioneering information However such indigenous radio programmes IRG are in most cases not likely to have been evaluated in terms of their influence on voters participation considering high level of perceived apathy during previous elections in Nigeria Therefore this study investigated influence of indigenous radio programmes contents of Splash FM s Oro Sun Nu Kun and Lagelu 96 7 FM s Bo se nlo on voters participation and voting patterns in the 2015 and 2019 governorship elections in Oyo State The study adopted a triangulation mixed-methods design of the convergent approach Sample comprised of 414 respondents including key informants drawn from Akinyele and Lagelu Local Government Areas of Oyo State Data was collected using three instruments Indigenous Radio Programme Contents Analysis Checklist InRaProCAC Voters Electoral Participation Questionnaire VEPQ r 0 0 0 760-0 861 and Key Electioneering Personalities Interview Schedule KEPIS Programme contents were analysed quantitatively while survey data was analysed using descriptive and inferential statistics Findings revealed that both Splash FM s Oro Sun nu kun and Lagelu FM s Bo se nlo adequately featured voter education contents prior to the 2015 and 2019 Governorship Election in Oyo State also majority of the respondents were regular listeners 82 2 89 7 and were adequately exposed 96 6 99 4 to the two indigenous radio programme contents with Splash FM recording higher exposure but Lagelu FM s featured more of voters education contents Av mean 3 51 Further findings revealed that there was an overall significant relationship in the electorates perception of featuring P 0 005 F1 22 voters education contents on both indigenous radio programmes In conclusion more voters participated during the two governorship elections as a result of their exposure to both indigenous radio programmes prior to the two governorship elections in Oyo State Therefore the study recommended that radio broadcasting stations should increase the strength of indigenous programmes for effective voters education
Keywords: radio broadcasting; radio programming; indigenous radio programmes